Factors Influencing Community Decisions in Choosing Edible-Nest Swiftlet Farming in Marioriwawo Subdistrict, Soppeng Regency: An Islamic Business Ethics Perspective - Sandi Sandi; Agus Salim HR; Idham Khalid (Green Economics: International Journal of Islamic and Economic Education, 2025)
This study aims to identify the factors that influence the local community in developing the swallow nest business and to examine how the practice of swallow nest farming aligns with the principles of Islamic business ethics in Marioriwawo District, Soppeng Regency. The swallow nest industry has grown significantly in this area, shifting the economic landscape from primarily agricultural activities to a more diversified business sector. Before the emergence of this business, most residents were involved in farming. However, due to factors such as unpredictable harvests and unstable agricultural income, many community members have turned to swallow nest cultivation as an alternative and promising source of livelihood. According to Islamic business ethics, the practice of breeding swallows is permissible, as long as it does not involve cruelty to animals. This view is supported by the Indonesian Ulema Council (MUI) Fatwa Number 2 of 2012, which states that raising or cultivating swallows is allowed, provided the birds are not harmed or subjected to distress. Furthermore, the consumption and trade of swallow nests are also considered halal under Islamic law, adding to the business's appeal among the Muslim population. To explore the underlying motivations and social dynamics of this business shift, the study employed a qualitative research method. This approach was chosen to gain a deeper understanding of the local context, including the experiences, beliefs, and socioeconomic conditions of the people involved. The results revealed several influencing factors: the potential for high profit from selling swallow nests, the challenges faced in traditional agriculture (such as frequent crop failure), and the religious assurance that the business is acceptable under Islamic teachings. Overall, the swallow nest business represents a strategic and ethical economic opportunity for the community, enabling them to improve their livelihoods while staying aligned with their religious values.